2019
DOI: 10.1590/1807-3107bor-2019.vol33.0070
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review on the effects of diabetes on implant failure and peri-implant diseases

Abstract: Tamires Szeremeske MIRANDA (a) Mariana Linhares ALMEIDA (a) Helio Doyle SILVA (a) Luciene Cristina FIGUEIREDO (a) Poliana Mendes DUARTE (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(103 reference statements)
0
11
0
2
Order By: Relevance
“…In five studies, no clear conclusion could be drawn from the data obtained, so that the question of an increased risk was not answered [ 10 , 25 , 33 , 43 , 64 ]. However, the available aggregated literature consistently concluded that diabetes mellitus represents a risk factor for the development of peri-implant inflammation, although most studies point to a lack of high-quality and long-term studies on this research area [ 8 , 50 , 51 , 54 56 , 58 , 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In five studies, no clear conclusion could be drawn from the data obtained, so that the question of an increased risk was not answered [ 10 , 25 , 33 , 43 , 64 ]. However, the available aggregated literature consistently concluded that diabetes mellitus represents a risk factor for the development of peri-implant inflammation, although most studies point to a lack of high-quality and long-term studies on this research area [ 8 , 50 , 51 , 54 56 , 58 , 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the study of Alberti et al [ 38 ] showed no significant difference of the implant survival after 10 years in patients with diabetes (survival rate of 96.5%) compared to patients without diabetes mellitus (survival rate of 94.8%), whereas the study of French et al [ 37 ] identified diabetes mellitus with a hazard ratio of 2.25 as a risk factor for implant failure in a multivariate analysis, implicating an over two times higher risk for failure of dental implants in patients with diabetes mellitus. In addition, eight aggregated literature references could be included on this question, whereby in seven publications, it was concluded that diabetes mellitus does not seem to have a significant influence on implant survival [ 8 , 51 , 52 , 55 58 , 63 ]. This includes two meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Efectos del ejercicio físico en pacientes con fibromialgia (22) Diabetes mellitus y complicaciones en implantes dentales (24)…”
Section: Urunclassified
“…Los autores incluyeron 10 RS. En otro caso, Mauricio et al (24) resumieron la evidencia sobre las asociaciones entre diabetes mellitus y complicaciones en implantes dentales. Los autores incluyeron 20 RS y ningún estudio fue de alta calidad metodológica.…”
Section: Ejemplos De Autores Latinoamericanosunclassified
“…In particular, excessive renal glucose reabsorption has been recognized as one of the main pathophysiological disorders in type 2 DM and a specific class of hypoglycemic agents SGLT2 inhibitors is now widely used to mitigate this phenomenon [14], in nerves, heart, and blood vessels [15][16][17][18]. It therefore represents a risk factor for many systemic and local pathologies including peri-implantitis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%